Effects of equine-assisted interventions on older adults' health: A systematic review - Léa Badin; Émilie Alibran; Kristell Pothier; Nathalie Bailly (Elsevier, 2022)
Objective: Equine-assisted interventions (EAI) can improve a variety of health problems in older adults and thus promote their well-being. This systematic review aimed to synthesize studies on EAI to understand better their effects on the health of older adults. Method: A systematic search guided by the PRISMA 2020 approach was performed on specific databases: Medline (PubMed), EMBASE, PsycINFO, and Cochrane Library. Peer-reviewed articles published in the English language from inception to June 2022 were retrieved. Methodological quality was established using the modified version of the Downs and Black checklist. Results: A total of 244 studies were retrieved, and 13 eligible studies were finally included. Three health domains were investigated: physical (balance, gait, and muscular strength), psychological (quality of life and cognitive assessment), and physiological (hormonal measures, cerebral and muscular activity). Among the eight studies investigating the physical dimension, four studies highlighted a positive effect of EAI on balance, four for gait, and three for strength. Regarding the three studies investigating the psychological dimension, two studies showed a positive effect of EAI on quality of life. Lastly, the four studies investigating the physiological dimensions all demonstrated a positive effect of EAI on hormonal measures and cerebral and muscular activity. Conclusion: Nevertheless, this systematic review provides promising findings regarding the positive effects of EAI on physical, psychological, and physiological health in older adults. Research on EAI should therefore be pursued rigorously to promote this non-pharmacological intervention in an older adult population.